Strategi Mempertahankan Usaha Kuliner Mikro di Air Terjun Temam Lubuk Linggau Terdampak Covid-19 - Pratama, Melati (Jurnal Ilmiah Pariwisata, 2022)
Covid-19 was a virus which is easy to infectious and can invade human for any age Covid-19 in Indonesia affected operational and income in many destinations especially micro culinary business actors. Air tejun temam Lubuk linggau was one of the destination affected. The objective of this research was to devise a strategy so that micro culinary business can continue to operate in the pandemic area. The descriptive with quantitative approach method was used in this research, that data was processed and analyzed by internal and external SWOT factors based on marketing functions. The result showed that internal and external factor of micro culinary in Air terjun temam destination at 3rd quadrant, which appropriate strategy to retain micro culinary business was rationalization strategy. Some of strategy that can used was made promotional event, which it can increase the number of tourists to Temam waterfall destination. The rationalization strategy was carried out by establishing cooperation between business actors and destination managers, fostering services for tourists that travel can still be done in the midst of a pandemic, fostering promotions, making policies about the tourists did not to bring food from outside and improvements to the quality of food. Keywords: SWOT Analysis, Micro Culinary Business; Covid-19